2013
DOI: 10.1007/s10943-013-9781-3
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Health: Anxiety, Religiosity, Meaning of Life and Mental Health

Abstract: We examined the association among anxiety, religiosity, meaning of life and mental health in a nonclinical sample from a Chinese society. Four hundred fifty-one Taiwanese adults (150 males and 300 females) ranging in age from 17 to 73 years (M = 28.9, SD = 11.53) completed measures of Beck Anxiety Inventory, Medical Outcomes Study Health Survey, Perceived Stress Scale, Social Support Scale, and Personal Religiosity Scale (measuring religiosity and meaning of life). Meaning of life has a significant negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 48 publications
4
32
1
7
Order By: Relevance
“…Results show that meaning in life has significant negative relationship with health anxiety. This is consistent with the findings of Dehghani et al [24] and Shiah and associates [25].…”
Section: Discussionsupporting
confidence: 94%
“…Results show that meaning in life has significant negative relationship with health anxiety. This is consistent with the findings of Dehghani et al [24] and Shiah and associates [25].…”
Section: Discussionsupporting
confidence: 94%
“…Historically, meaning in life is one of the most controversial issues in psychology and philosophy. So far, some efforts have been made to understand its nature over the centuries and great philosophers and psychologists such as Nietzsche, Sartre, Frankl, Yalom and … discussed it (Loffler et al, 2010;Shiah et al, 2015). A religious culture considered meaning in life as important and it becomes one of the most important components of philosophical problems in moral philosophy.…”
Section: Introductionmentioning
confidence: 99%
“…Meaning in life component is one of the important philosophical issues not only because of its nature but also due to its necessity and requirements. Although many uncertainties and questions found in this issue, psychologists and philosophers of ethics have always shown great interest in this topic and have tried to answer these questions (Reynolds & Turner, 2008;Shiah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The above theoretical arguments and studies indicate that transgression, being open for eternal values and towards the supernatural reality helps to increase a sense of purpose and satisfaction with life [38]. It has also been indicated that the sole acceptance of God's existence and religious involvement (one of the aspects of religiosity) help to find the meaning of life.…”
Section: Scheme 1 Theoretical Model Of Miraculous Healings Beliefs (mentioning
confidence: 97%